Dekompozycja błędu klasyfikacji w zagregowanych modelach dyskryminacyjnych - Rozmus, Dorota (Error Decomposition in Aggregated Discriminant Models, 2005)
The idea of error decomposition comes from regression where the square loss function is applied. Prediction error is decomposed into three components: noise, bias and variance. There are also trials to apply the idea of error decomposition in classification. But the sum of those three components is different to the value of classification error. This is why several authors have proposed their own definitions of decomposition components for classification problem. In this paper we present and compare known decompositions for 0-1 loss.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 274-282